Robot-assisted excision of hemangioma of the right renal vein - Francesca Montanaro; Riccardo Bertolo; Sonia Costantino; Nicola De Maria; Alessandro Veccia; Filippo Migliorini; Anna Caliò; Matteo Brunelli; Stefania Montemezzi; Maria Angela Cerruto; Alessandro Antonelli (Urology Case Reports, 2024)
Hemangiomas, benign vascular masses, occasionally occur in the kidneys, presenting as rare, small, unilateral, and solitary growths. Venous hemangiomas, a renal subtype, are atypical. While clinically nonspecific, they are typically asymptomatic and may be incidentally discovered during unrelated clinical workups. Diagnosing renal hemangioma preoperatively is challenging due to rarity, lacking standard radiographic criteria, and poor differentiation from aggressive renal neoplasms on contrast-enhanced imaging. These tumors commonly follow a benign course, with no documented recurrence. This video article showcases the robot-assisted excision of a renal vein hemangioma, addressing the expertise needed in managing this uncommon condition robotically.